Escolas de governo e escolas de serviço público: limites e problemas (Estudo de Caso da FESP/RJ e FUNDAP/SP) - Orban, João Soares (2001)
This work seeks to identify a specifc field to institutions connected to the Stat Governrnent that act with professional competence and are named Govemment Schools. Takes as study case the experiences of FUNDAP, in São Paulo and FESP, in Rio de Janeiro and from a criticaI anaIysis about your way of working, conception and paradigm. Seeks to signal new ways to consolidate these institutions in Brazil. Examines a model adapted from National School of Administration, ENAP, that serves of reference to the Governrnent Schools studied, seeking to identify the existing troubles from these institutions and show that these are situated much Iess in quaIity of performance of their activities - courses and programs of professional competence and yes in conception and mission.